Human-computer interaction : interaction technologies : 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: interaction technologies : 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part III (2018) - Unknown
No abstract available